A Medical Outreach Elective Course - Perry, Elizabeth (American Journal of Pharmaceutical Education, 2013)
Objective. To design and implement a Medical Outreach Experience elective course and assess its impact on students’ level of confidence in organizing future medical outreach trips, providing population-specific pharmaceutical care, and achieving learning outcomes. Design. A 2-credit hour elective course was designed for second- and third-year pharmacy students. The course was structured to include 3 sections over 1 semester, a 10-week training and preparation phase, followed by a weeklong international outreach experience and post-outreach reflection. Assessment. Student achievement of curricular outcomes was measured using in-class activities, readings, reflections, and longitudinal projects, as well as performance during the outreach trip. Results from pre- and post-course surveys demonstrated significant improvement in student-rated confidence in several components of outreach trip organization and provision of pharmaceutical care. Conclusions. Students completing the course exhibited increased confidence in their abilities to organize and practice on a medical outreach trip. All students met the learning outcomes of the course, which included providing comprehensive patient-specific pharmaceutical care, communicating effectively, promoting health improvement and self-care, thinking critically, and appropriately managing and using resources of the healthcare system. Students agreed that the elective course was a valuable addition to the curriculum.